Left Ventricular Ejection Fraction Is Associated with the Risk of Thrombus in the Left Atrial Appendage in Patients with Atrial Fibrillation - Beata Uziębło-Życzkowska; Paweł Krzesiński; Agnieszka Jurek; Agnieszka Kapłon-Cieślicka; Iwona Gorczyca; Monika Budnik; Grzegorz Gielerak; Marek Kiliszek; Monika Gawałko; Piotr Scisło; Janusz Kochanowski; Olga Jelonek; et al. (Hindawi-Wiley, 2020)
Introduction. Atrial fibrillation (AF) is associated with high risk of ischemic stroke. The most frequent thrombus location in AF is the left atrial appendage (LAA). Transthoracic echocardiography (TTE) is a basic diagnostic examination in patients (pts) with AF. Objectives. To analyse the relations between basic echocardiographic features, well-established stroke risk factors, type of AF, and anticoagulation therapy with the incidence of left atrial appendage thrombus (LAAT). Patients and Methods. The study group consisted of 768 pts with AF (mean age, 63 years), admitted to three high-reference cardiology departments. Five hundred and twenty-three pts were treated with non-vitamin K antagonist oral anticoagulants (NOACs) and 227 (30%) with vitamin K antagonists (VKAs). The subjects underwent TTE and transesophageal echocardiography (TEE) before cardioversion or ablation. Results. LAAT was significantly more frequent in pts with reduced left ventricular ejection fraction (LVEF): in 10.6% (7 pts) with LVEF<40% and in 9.0% (9 pts) with LVEF 40-49%, while only in 5.5% (33 pts) with LVEF>50%. Compared to pts without LAAT, those with LAAT presented with lower LVEF and higher left atrial diameter (LAD). Multivariate logistic regression revealed the following variables as independent predictors of LAAT: previous bleeding, treatment with VKA, and LVEF. Conclusion. LAAT is related to lower LVEF and higher LAD. LVEF is one of the independent predictors of LAAT. Even in the case of adequate anticoagulant therapy, it might be prudent to consider TEE before cardioversion or ablation in patients with low LVEF and LA enlargement, especially in the coexistence of other thromboembolic risk factors.